MENGOPTIMALKAN KURIKULUM MERDEKA UNTUK MENINGKATKAN EFEKTIVITAS PENGAJARAN DI SEKOLAH DASAR - Cyndi Togi Marito Sitorus; Wafi Lathifah Miranty; Yola Amanda; M. Jaya Adiputra; Mauliatun Nisa (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research examines the optimization of the Merdeka Curriculum as a learning plan to enhance teaching effectiveness in elementary schools. The Merdeka Curriculum, introduced in response to modern educational demands, offers a more flexible and learner-centered approach. This study investigates the challenges and opportunities in integrating the principles of the Merdeka Curriculum into daily teaching practices, focusing on the development of core competencies such as literacy, numeracy, and character. The research methodology involves qualitative analysis of curriculum implementation in various elementary schools, interviews with educators, and classroom observations. The findings indicate that optimizing the Merdeka Curriculum requires a paradigm shift in teaching, enhancement of teachers' skills in designing contextual learning, and ongoing evaluation and adjustment of teaching strategies. The study concludes that with the right approach, the Merdeka Curriculum can serve as an effective catalyst for improving the quality of learning in elementary schools, preparing students to face the challenges of the 21st century.